A New Pathway To Enhance The Nuclear Security Regime - Francesca Giovannini (International Journal of Nuclear Security, 2016)
The paper investigates the approach used by a new set of regional institutions, the Disaster Preparedness and Risk Management Organizations (DPRMOs), in strengthening regional governance and cooperation. It also inquires in what ways these new institutions might indirectly contribute to the establishment of a more cohesive global nuclear security framework. More specifically, through the examination of the case of Southeast Asia, the paper argues that these institutions, albeit without a specific and direct mandate to operate in the nuclear security domain, are fundamentally strengthening states’ capacity to assess risks and threats and to map vulnerabilities in timely fashion. They are also encouraging the development of a tight information-sharing network to allow countries to harmonize their preventive and management responses to disasters (both natural and man-made). The approach used by these organizations might well complement the current approach to nuclear security which came into being with the launch of the UN Resolution 1540 and the global initiatives that followed suit. To be successful, the paper asserts, the current approach relies on the expectation that states will be willing to undertake significant changes in their political, economic and social institutional infrastructures so as to tackle the underlying causes of vulnerability to nuclear terrorism. Yet this current approach does not seem to provide states with the ultimate rationale for underwriting these comprehensive changes within their domestic institutional landscape mostly because the threat of nuclear terrorism is defined in universal terms, independent of each state’s unique context. The approach offered by DPRMOs instead departs from the fundamental premise that countries will respond to risks and threats with adequate resources only if and when they become aware of their internal vulnerabilities to such risks. This model therefore supports the national-level development of accurate and rigorous risk assessments on which state responses will be later designed. The topic of this paper is particularly timely. The nuclear security agenda has attracted considerable attention worldwide, galvanized countries and nuclear agencies, and gathered momentum through the Nuclear Security Summits. Yet in parallel to this record of successful achievements, nuclear security has also attracted resistance, skepticism, and overall obstructionism by some countries who have perceived it as a means for the United States to restrict emerging markets from gaining access to nuclear technology. Even more worrisome, the reaction of regional organizations to the nuclear security agenda has been lukewarm at best. Regions and their institutions have a fundamental role to play in ensuring that nuclear security becomes one of the fundamental pillars of good nuclear governance, but the underdeveloped regional dimension of nuclear security governance is a significant problem. It has been widely acknowledged that nuclear security risks are fundamentally collective problems emanating from weak border control, frail export control policies, and insufficient regional security regulations. In some regional contexts, such as in South America and in Southeast Asia, regional organizations have offered poor leadership but often have been paralyzed by internal political disputes among member states supporting the nuclear security agenda and others opposing it. The new collective approach that DPRMOs are offering will greatly strengthen collaboration and regional governance and will ultimately solidify national nuclear security policies.
Keywords: governance; security; regional powers; Southeast Asia; crisis; disasters